A Potential Compensatory Role of Panx3 in the VNO of a Panx1 Knock Out Mouse Model - Whyte-Fagundes, Paige; Kurtenbach, Stefan; Zoidl, Christiane; Shestopalov, Valery I.; Carlen, Peter L.; Zoidl, Georg (Frontiers in Molecular Neuroscience, 2018)
Pannexins (Panx) are integral membrane proteins, with Panx1 being the best-characterized member of the protein family. Panx1 is implicated in sensory processing, and knockout (KO) animal models have become the primary tool to investigate the role(s) of Panx1 in sensory systems. Extending previous work from our group on primary olfaction, the expression patterns of Panxs in the vomeronasal organ (VNO), an auxiliary olfactory sense organ with a role in reproduction and social behavior, were compared. Using qRT-PCR and immunohistochemistry, we confirmed the loss of Panx1, found similar Panx2 expression levels in both models, and a significant upregulation of Panx3 in mice with a global ablation of Panx1. Specifically, Panx3 showed upregulated expression in nerve fibers of the non-sensory epithelial layer in juvenile and adult KO mice and in the sensory layer of adults, which overlaps with Panx1 expression areas in WT populations. Since both social behavior and evoked ATP release in the VNO was not compromised in KO animals, we hypothesized that Panx3 could compensate for the loss of Panx1. This led us to compare Panx1 and Panx3 channels in vitro, demonstrating similar dye uptake and ATP release properties. Outcomes of this study strongly suggest that Panx3 may functionally compensate for the loss of Panx1 in the VNO of the olfactory system, ensuring sustained chemosensory processing. This finding extends previous reports on the upregulation of Panx3 in arterial walls and the skin of Panx1 KO mice, suggesting that roles of Panx1 warrant uncharacterized safeguarding mechanisms involving Panx3.